Correlation of Measures of Cerebral Autoregulation After Subarachnoid Hemorrhage. (16th November 2020) - Owen, Bryce; Fritch, Chanju; Carlson, Andrew P
Abstract: INTRODUCTION: Large vessel vasospasm has long been thought to be the primary mechanism of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). Rising evidence suggest that other mechanisms of injury such as impaired cerebral autoregulation (CA) and spreading depolarization contribute to patient mortality and poor neurologic outcomes. However, there is little agreement on how and when to measure CA in patients with aSAH. Studies have used different modalities and time frames to assess autoregulation status, leading to conflicting heterogeneity in the literature. METHODS: 32 patients were enrolled into this prospective observational study and received institutionally standardized multimodal monitoring. Simultaneous measurement of intracranial pressure (ICP), Bowman cerebral blood flow (CBF), bilateral scalp oximetry (NIRS), and LiCox tissue oxygenation were available from 18 patients. The Pearson correlation coefficient between each measure and MAP was generated to estimate a reactivity index. In this manner, pressure reactivity (PRx) (the most widely used measure) was compared against a CBF reactivity (CBFrx), total hemoglobin reactivity index from NIRS (THx), and oxygenation reactivity from Licox (ORx). Bland-Altman plots were used as tests of correlation between measures. RESULTS: The average difference (bias) between PRx and the other CA measures ranged from −0.023 to +0.032. However, there was poor statistical correlation between measures, with CBFRx showing good correlation with PRx in just 5%(1), ORx 11%(2), and THx 16% (3). The bias between MAPopt derived from PRx compared with MAPopt derived from CBFRx displayed the highest level of concordance (bias of +0.14 mmHg), with the other measures demonstrating a slightly greater degree of bias (ORx = −11.4 mmHg, THx = 4.5 mmHg). CONCLUSION: This is a first cohort of aSAH patients to have obtained prospective simultaneous PRx, CBFRx, ORx, and THx data. We demonstrate here that there is poor correlation between the absolute value of these reactivity indexes, although they retain the same ability to predict a similar value of optimal MAP. Further studies are needed to assess the ability of these novel CA measures to predict morbidity and mortality.